(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article explores the influence of traditional folk dances on contemporary choreography. It delves into how folk dance, as a cultural and historical form, provides a rich source of inspiration for modern choreographers. By blending traditional movements and rhythms with contemporary dance techniques, choreographers create innovative performances that reflect both cultural heritage and modern artistic expression. The article highlights the fusion of folk and contemporary dance, the role of music and rhythm, and the global impact of cultural exchange in the world of dance. It also addresses challenges such as cultural appropriation, emphasizing the importance of respecting and collaborating with folk traditions.